HADITH AND CONTEMPORARY RELIGIOUS MOVEMENTS: SEARCHING FOR HUFFAZ SCORING MOVES - Acim, Subhan Abdullah; Sugiarto, Fitrah; Ahlan, Ahlan (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
The phenomenon of religious movements that occur in Indonesia is very diverse, both related to behavior directly, as well as readings such as blessings, dhikr, and others. This phenomenon is the result of the interpretation of the arguments that become beliefs, one of which is Hadith. This article discusses the phenomenology of contemporary religious movements based on online media with specifications on presenting huffadz al-Qur'an. The process in finding the data using a phenomenological approach is then displayed in descriptive. The purpose of this article is to describe the contemporary movement of scholars printing Huffaz, with a focus on Yayasan Tahfiz Online Indonesia and Rumah Tahfiz Darul Qur'an as well as its advantages and disadvantages. In the further process, the author will analyze the shifts that occur in the two systems. The results of the study are : Tahfiz Online is a program designed to help people who want to learn and memorize the Qur'an online. 2). The Impact or influence that occurs later on the basis of mass media is on the ease of access to students with a wide range, flexible time and place because students do not have to mukim, and can be run by working. Finally, the impact is a shifting orientation.